2012
DOI: 10.1155/2012/653608
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Accuracy of Platelet to Lymphocyte Ratio after Adjustment for Large Platelet Count: A Pilot Study in Breast Cancer Patients

Abstract: Background. The objective of our study is to investigate the potential effect of adjusting preoperative platelet to lymphocyte ratio, an emerging biomarker of survival in cancer patients, for the fraction of large platelets. Methods. A total of 79 patients with breast neoplasias, 44 with fibroadenomas, and 35 with invasive ductal carcinoma were included in the study. Both conventional platelet to lymphocyte ratio (PLR) and the adjusted marker, large platelet to lymphocyte ratio (LPLR), were correlated with lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Patients with a higher platelet-to-lymphocyte ratio experienced poorer survival times (15,16,21) and a larger number of infiltrated lymph nodes (22) compared with patients with a lower platelet-to-lymphocyte ratio. By contrast, Ulas et al (20) and Yao et al (18) reported that platelet-to-lymphocyte ratio does not significantly affect survival times in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 91%
“…Patients with a higher platelet-to-lymphocyte ratio experienced poorer survival times (15,16,21) and a larger number of infiltrated lymph nodes (22) compared with patients with a lower platelet-to-lymphocyte ratio. By contrast, Ulas et al (20) and Yao et al (18) reported that platelet-to-lymphocyte ratio does not significantly affect survival times in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 91%
“…There are some studies about PLR and periampullary cancer in the literature but reports are not satisfactory 18,19 . There are valuable results in the studies about the role of PLR in terms of prognosis of the patients with breast and gynaecological malignancies 12,13,20,21 . The predictive values of PLR in patients with myocardial infarction, peripheral arterial occlusive disease, and end-stage renal diseases were also studied [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…In many types of cancer and inflammatory processes, the release of proinflammatory cytokines promotes magakaryocytes' proliferation. The activation of platelets is a hallmark in the natural course of cancer, by promoting neoangiogenesis, degradation of extracellular matrix, release of adhesion molecules, and growth factors 12,13 . Lee et al demonstrated that NLR or PLR were independent prognostic factors for overall survival with …”
Section: Discussionmentioning
confidence: 99%
“…To be more specific, this reactive thrombocytosis is an qualitative turning point, as it does not only have a quantitative substance (maintenance of the total platelet count within the normal range), since the newly formed, immature platelets are enzymatically more active than the mature ones; the reason is that the immature platelets contain more granules in their cytoplasm and have a rounder shape, fact which facilitates the exposure of their surface receptors [43,44]. Therefore, even in the absence of an abnormal total platelet count, cancer progression results in the presence of an increasing percentage of activated platelets, triggering a vicious circle of hypercoagulation-induced cancer spread and cancer-induced hypercoagulation.…”
Section: Colorectal Cancer-induced Hypercoagulationmentioning
confidence: 99%